The Role of Diffuse Electron Precipitation in the Formation of Subauroral Polarization Streams. Issue 12 (5th December 2021) - Lin, Dong; Sorathia, Kareem; Wang, Wenbin; Merkin, Viacheslav; Bao, Shanshan; Pham, Kevin; Wiltberger, Michael; Shi, Xueling; Toffoletto, Frank; Michael, Adam; Lyon, John; Garretson, Jeffrey; et al.
Abstract: The role of diffuse electron precipitation in the formation of subauroral polarization streams (SAPS) is investigated with the Multiscale Atmosphere‐Geospace Environment (MAGE) model. Diffuse precipitation is derived from the distribution of drifting electrons. SAPS manifest themselves as a separate mesoscale flow channel in the duskside ionosphere, which gradually merges with the primary auroral convection toward dayside as the equatorward auroral boundary approaches the poleward Region‐2 field‐aligned currents (FACs) boundary. SAPS expand to lower latitudes and toward the nightside during the main phase of a geomagnetic storm, associated with magnetotail earthward plasma flows building up the ring current and intensifying Region‐2 FACs and electron precipitation. SAPS shrink poleward and sunward as the interplanetary magnetic field turns northward. When diffuse precipitation is turned off in a controlled MAGE simulation, ring current and duskside Region‐2 FACs become weaker, but subauroral zonal ion drifts are still comparable to auroral convection. However, subauroral and auroral convection manifest as a single broad flow channel without showing any mesoscale structure. SAPS overlap with the downward Region‐2 FACs equatorward of diffuse precipitation, where poleward electric fields are strong due to a low conductance in the subauroral ionosphere. The Region‐2 FACs extend to latitudes lower than the diffuse precipitation because the ring current protons penetrate closer to the Earth than the electrons do. This study reproduces the key physics of SAPS formation and their evolution in the coupled magnetosphere‐ionosphere during a geomagnetic storm. Diffuse electron precipitation is demonstrated to play a critical role in determining SAPS location and structure. Plain Language Summary: Subauroral polarization streams (SAPS) are a mesoscale (∼100–500 km) plasma flow channel frequently observed in the duskside subauroral ionosphere. This study investigates how diffuse electron precipitation affects the location and structure of SAPS, using the newly developed, state‐of‐the‐art geospace model of Multiscale Atmosphere‐Geospace Environment (MAGE). The MAGE model has the capability to directly simulate diffuse precipitation using particle drift physics. MAGE numerical experiments show that SAPS exhibit as a separate flow channel when diffuse precipitation is included in the simulation, but subauroral and auroral convections become one broad channel when diffuse precipitation is turned off. SAPS are produced in the gap region between the low latitude boundaries of electron aurora and downward field‐aligned current (FAC) on the duskside, where the ionospheric conductance is low due to lack of ionization while downward region‐2 FAC closes through this low conductance region. Strong poleward electric fields are generated to drive large westward ion drifts in the SAPS channel. Tracing back to the magnetosphere, the gap between the inner boundaries is formed because the ring current protons, whose distribution primarily determines the downward FAC, penetrate deeper than the electrons. Thus diffuse aurora, with plasma sheet as the source population, occurs poleward of the lower boundary of the downward Region‐2 current. This study demonstrates the importance of including diffuse precipitation in coupled geospace models to understand the dynamics of SAPS. Key Points: A fully coupled geospace model captures the key physical mechanism and distinct spatial structure of subauroral polarization streams The separation of the flow channel from the main auroral convection is determined by diffuse electron precipitation boundary The evolution of the SAPS in the ionosphere and magnetosphere is reproduced by the simulation in accordance with observations